Animal models of necrotizing enterocolitis. Issue 1 (25th March 2020) - Mendez, Yomara Stephanie; Khan, Faraz A; Perrier, Gregory Van; Radulescu, Andrei
Abstract : Background: Necrotizing enterocolitis (NEC) is one of the leading causes of death in premature infants. To determine the factors present in the disease that lead to increased morbidity and mortality, manipulation of variables that are shown to have a positive response has been tested using various animal models. Testing and manipulation of these variables are unwarranted in humans due to regulatory health standards. Methods: The purpose of this review is to provide an update to previous summaries that determine the significance of animal models in studying the mechanisms of NEC. A large variety of animal models including rats, mice, rabbits, piglets, nonhuman primates, and quails have been described in literature. We reviewed the reported animal models of NEC and examined the pros and cons of the various models as well as the scientific question addressed. Results: The animals used in these experiments were subject to gavage feeding, hypoxia, hypothermia, oxygen perfusion, and other methods to induce the disease state. Each of these models has been utilized to show the effects of NEC on the premature, undeveloped gut in animals to find a correlation to the disease state present in humans. We found specific advantages and disadvantages for each model. Conclusions: Recent advances in our understanding of NEC and the ongoing therapeutic strategy developments underscore the importance of animal models for this disease.